Islam, State and Society in Indonesia: Local Politics in Madura - Mardiana, Dina; Umiarso, Umiarso (Journal of Islamic Educational Research, 2020)
ISLAM, the state, and society as a social construction can be studied through various spectrums of thought, including through the study of the sociology of religion that interprets the religious dimension as it is. The consequence of the interpretation of sociology of religion and local history then necessitates variants of understanding, religious experience and world view in the midst of society, including aspects of relations between the state and society; between Islam and politics; even the role of the state in the midst of Muslim culture. This point became the initial foundation of this book entitled â€œIslam, State and Society in Indonesiaâ€.